FISHING TECHNOLOGY CONVERSION, DIFFERENTIATION, AND SOCIAL MOBILITY OF FISHERMAN IN LAGASA VILLAGE OF MUNA REGENCY - Awaluddin Hamzah; Muhammad Aswar Limi; La Nalefo La Nalefo; Abdul Gafaruddin (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2015)
The modernization through the improvement, the application of technology of fishing utility, the funding support which affects on the activity and organization of fisherman and eventually causes the transformation in the society. The aim of this research was to analyze the impact of fishing technology conversion to social structure of Bajo tribe fisherman. The methods used to collect the primer and secondary data from informant were: completed questionnaire, deep interview with both informants and respondents, and live observation (participate observation). Analysis of data was performed descriptively which is concept development, collect the evidences but did not perform the hypothesis trial, and analyze the variable relationship for hypothesis testing by applying the quantitative and qualitative tabulation. The results of this research was the fishing technology conversion in fisherman society brings up many impacts on various aspects in fisherman’s life. The application of every type old technology affected on the consequences or impacts such as the work pattern, social structure, and the fisherman prosperity level. The relationship between the ponggawa as the owner of production utility and the sawi as the worker is not the exploitative characteristic, because both of them still apply the cultural values which help each other not only in teamwork but also in relationship pattern in their daily life. So that the characteristic of the relationship pattern is not exploitative and require each other. The difference does not show the polarization indication because the Bajo tradition to help each other is still applied.